Selective Removal of Anionic and Cationic Dyes Using Magnetic Composites - Fitri, Erni Salasia; Mohadi, Risfidian; Palapa, Neza Rahayu; Susila Arita Rachman; Lesbani, Aldes (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Water is one of the most basic human needs, and dyes are one of the sources of water pollution. Since adsorption has proven to be effective in removing contaminants, it is the most widely used technique. In this adsorption, a LDH Zn-Al /magnetic biochar composite was used for dye removal. Zn-Al LDH, magnetic biochar, and LDH Zn-Al/biochar magnetic composite were successfully synthesized, based on XRD and FTIR studies. XRD analysis of the Zn-Al LDH material shows diffractions of (003), (006), (101), (012), (015), (107), and (110) around the 2theta angle at 10.29°, 20.07°, 29.59°, 32.12°, 34.02°, 48.06°, and 60.16° which are characteristic of LDH materials. In magnetic biochar and LDH Zn-Al/magnet biochar composites diffraction (220), (311), (422) and (440) at 2theta around 24.9°, 35°, 63° and 68.4° in these materials indicate the characteristics of carbon-based materials from biochar. FTIR analysis showed the appearance of a vibration peak at 1404cm−1 indicating the presence of C H groups contained in biochar. The characteristic double-layer hydroxy (M-O) vibrations below 1000 cm−1 also indicated that the composite preparation process had been successful. The study’s results show that cationic dyes are more easily adsorbed than anionic dyes. Specifically, the LDH Zn-Al/Magnetic Biochar composite more extensively absorbs the cationic dye malachite green.